Novel diagnostics for the study of electron transport in solid materials - Koester, P; Lancaster, K; Evans, R; Koenig, M; Baton, S; Gizzi, L; Batani, D; Woolsey, N; Norreys, P; Green, J; Perez, F; Morace, A; et al. (2007)
The study of fast electrons generated in laser-matter interactions and their transport through matter is of great interest for the fast ignition concept in the inertial confinement fusion. A typical experimental approach is the interaction of intense laser radiation with foil targets. The transport of the electrons through the foil can be studied with several techniques including X-ray emission measurements and direct measurements on electrons leaving the foil. Some laser-matter interaction features can be monitored using spectroscopy in the visible range. Here we will focus our attention on some of the experimental techniques that have been used in laser-foil experiments at ILIL laboratory in Pisa and in a VULCAN Petawatt experiment at RAL. In particular we will describe high resolution X-ray spectroscopy with a bent crystal, K-alpha flux measurements, direct measurements of the angular distribution and spectrum of the electrons, and spectroscopy of the 3/2ω and 2ω harmonics of the laser radiation.